(untitled) (Minerva. Revista de Filología Clásica, 2020)
Reseña de Alessandra Foscati, Saint Anthony’s Fire from Antiquity to the Eighteenth Century, Amsterdam, Amsterdam University Press, 2020, 264 páginas, ISBN 978-94-6298-334-2